Dynamic vulcanisation of EPDM-Based thermoplastic vulcanisates during extrusion : effect of processing conditions - Machado, A. V. (2006)
Dynamic vulcanisation of EPDM/PE blends using the resol/SnCl2 system was studied in a co-rotating twin screw extruder using a series of sampling devices. In order to study the effect of the processing conditions on chemical development along the extruder and on the mechanical properties of the extrudate material, the same recipe (having the same polyolefin/EPDM ratio) was compounded under different processing conditions. The results showed that both chemical evolution and mechanical properties depend on the processing conditions.